Analisis Driving Awareness Pengendara Sepeda Motor Menggunakan Structural Equation Modeling - Mauliana, Risma; Hawari, Rifat Aditya; Reni Maria; Cut Sitti Rafidatul Hildayani; Yusri, Queen Monalisa (Universitas Iskandar Muda, 2026)
Road safety plays an important role in reducing the risk of traffic accidents among motorcycle riders. This study aimed to analyze the factors influencing the driving awareness of motorcycle riders in Ingin Jaya District, Aceh Besar Regency. A quantitative approach was employed involving 155 respondents selected using purposive sampling. Data were collected through a four-point Likert scale questionnaire and analyzed using Structural Equation Modeling (SEM) with Confirmatory Factor Analysis (CFA). The findings showed that the proposed model satisfied the goodness-of-fit criteria. Riding safety had a positive and significant effect on safety attribute awareness (t = 3.82), while safety attribute awareness significantly influenced driving awareness (t = 4.39). The results indicate that improving safe riding behavior and increasing compliance with safety equipment contribute to better driving awareness among motorcycle riders. These findings provide useful information for developing road safety education programs and supporting traffic safety improvement strategies.